Current Trends in Cleft Lip and Palate Publications During the Last 10 Years: A Bibliometric Analysis - Ebru Yurdakurban; Serkan Görgülü; Gökhan Serhat Duran; Rüveyda Doğrugören (Selçuk University, 2022)
Objective: The purpose of this study is to investigate the apparent trends in cleft lip and palate (CLP) studies published over the last 10 years, and assesses the effectiveness of the studies. Materials and Methods: The SCImago Journal Rank (SJR) data were utilized to select the journals with a high SJR indicator in each of the orthodontics, pedodontics, general dentistry, speech therapy, clinical genetics, pediatrics, plastic esthetic and reconstructive surgery and oral surgery areas. CLP-related studies were identified in the databases accessed through Web of Science owned by Clarivate Analytics. The articles were assessed in terms of year of publication, journal title, specialty, article subject matter, affiliations of the authors, citation relationships and countries/regions of origin. A total of 2,696 CLP-related articles published over the last 10 years were identified based on our search criteria. Results: The analysis revealed that the most prominent keywords were "palatoplasty", "alveolar bone grafting", "distraction osteogenesis" and "orthognathic surgery" among the treatment procedures. The most common WoS categories among the articles were dentistry, oral surgery & medicine, and surgery. The most cited publications over the last decade have included such terms as "environmental risk factor", "GRHL3", "FGFR2", "loci", "candidate gene" and "BMP". Conclusion: Recent CLP articles in the literature have focused mainly on treatment procedures, with the most-cited articles generally containing evaluations of the relationship between CLP and genetics. More recent methods have been discussed in only a limited number of studies.